1999
DOI: 10.1038/sj.bjp.0702309
|View full text |Cite
|
Sign up to set email alerts
|

Improvement by nefiracetam of β‐amyloid‐(1‐42)‐induced learning and memory impairments in rats

Abstract: 1 We have previously demonstrated that continuous i.c.v. infusion of amyloid b-peptide (Ab), the major constituent of senile plaques in the brains of patients with Alzheimer's disease, results in learning and memory de®cits in rats. 2 In the present study, we investigated the e ects of ne®racetam [N-(2,6-dimethylphenyl)-2-(2-oxo-1-pyrrolidinyl) acetamide, DM-9384] on Ab-(1-42)-induced learning and memory de®cits in rats. 3 In the Ab-(1-42)-infused rats, spontaneous alternation behaviour in a Y-maze task, spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 52 publications
12
56
0
Order By: Relevance
“…CLN treatment attenuated contextual memory impairment caused by Ab detected in PA as well as Ab-induced spatial working memory impairment in YM. As reported in earlier studies (Yamada et al, 1999, i.c.v. injection of Ab downregulates the expression level of ChAT in neurons of the medial septum.…”
Section: Intranasal Administration Of Cln Protects the Cholinergic Sysupporting
confidence: 80%
See 1 more Smart Citation
“…CLN treatment attenuated contextual memory impairment caused by Ab detected in PA as well as Ab-induced spatial working memory impairment in YM. As reported in earlier studies (Yamada et al, 1999, i.c.v. injection of Ab downregulates the expression level of ChAT in neurons of the medial septum.…”
Section: Intranasal Administration Of Cln Protects the Cholinergic Sysupporting
confidence: 80%
“…Intracerebroventricular injection of toxic Ab peptides has been reported to impair spatial working memory in rodents (Maurice et al, 1996;Yamada et al, 1999Yamada et al, , 2005. We have recently established a toxic Ab-induced mouse model of AD by using repetitive i.c.v.…”
Section: Intranasal Administration Of Cln Protects the Cholinergic Symentioning
confidence: 99%
“…Intracerebroventricular injection of toxic A␤ peptides has been reported to impair spatial working memory in rodents (Flood et al, 1991;Delobette et al, 1997;Yamada et al, 1999;Yamaguchi and Kawashima, 2001;Stepanichev et al, 2003b). Although administration of A␤ into cerebral ventricles has usually been performed by a one-shot or bolus intracerebroventricular injection of a large dose of A␤, rats with dementia have been constructed successfully by continuous infusion of A␤ via an osmotic pump connected to the cerebral ventricle (Nitta et al, 1997; Yamada et …”
Section: In Vivo Effect Of Colivelin On Impairment In Spatial Workingmentioning
confidence: 99%
“…The bamyloid (Ab) peptide that comprises senile plaques induces brain dysfunction, as evidenced by neurodegeneration and learning and memory impairment in rodents. [1][2][3][4][5][6] Several reports have demonstrated that Ab 1-40 , Ab and Ab [25][26][27][28][29][30][31][32][33][34][35] proteins impaired learning and memory to the same extent. 1,4,5) Similarly, Terranova et al have shown that those three proteins induce the cognitive dysfunction in rats.…”
mentioning
confidence: 99%